Penggunaan Grup Whatsapp Sebagai Media Komunikasi Remaja Islam Wonorejo Malang - Hamdan Yuwafik; Abdul Muhid (KOMUNIDA : Media Komunikasi dan Dakwah, 2020)
This paper describes how to use the WhatsApp group as a communication medium for the Riswo Village Druju Sumbermanjing Wetan Malang. It is a descriptive qualitative research using the approach of organizational communication. This study uses face negotiation theory. This theory uses the concept of facework as a verbal and nonverbal strategy that is used to maintain, maintain or enhance social self-image or attack, maintain the social image of others. The results of the study explain that the management of the Druju Village Riswo uses solidarity facework and sensitivity facework in communicating through the WhatsApp application in running the organization's wheels. Organizational communication carried out by Riswo Village management of Druju Sumbermanjing Wetan Malang in accordance with organizational communication functions including, informative, regulative, persuasive and integrative functions. The target audience of the Drwo Village Riswo administrators in this study were all the Drwo Village Riswo administrators who had been recruited and became part of the Riswomprogram Riswomilik Pesuju management group of Druju Village. There are three uses of the WhatsApp group as an organizational communication medium. First, it is more efficient in terms of time, space and resources. Second, it facilitates participation, understanding and reception of messages, and third, satisfaction in the use of WhatsApp groups.